EFFECTIVENESS OF ROLE PLAYING MODE IN THE SKILL SPEECH LEARNING - Rahmawati, Sitta Fauziah Nur; Mustofa, Syaiful (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
Speaking is a second skill after listening that means of communication with other people. In education, speaking skill is being one of skill less interesting student, because the role of student a little in this learning, less confidence of the student and less application of method and strategy creation in this learning impressed which was dominated by a teacher. The researcher found of the problem in State Islamic High School 2 of Gresik that majority student felt bored and not able to speak in Arabic. Therefore, the researchers tried to using the role playing mode in speaking learning. Based on the problem above, the researcher proposed as follows: 1. How to use the role playing mode, 2. How the effectiveness of using role playing mode to enhance the speech ability in State Islamic High School 2 of Gresik. The study design used experiment research with a quantitative analysis and collected data was obtained through observation, interview, test, and documentation. The result from these studies are as follows: 1. Steps applied the role playing mode are: (a) the teacher devised a scenario learning, (b) a teacher pointed students to study the scenarios before learning, (c) teachers formed student group which consists of six peoples, (d) a teacher called a student has been appointed to showcase scenarios, (e) each students observed a scenario with his group, (f) the teacher gave the general conclusion. 2. The result of t-test = 4,08 is  the greater than the result t.s 0,05 = 1,711 and t.s 0,10 = 1,318 which mean H a and this research hypothesis was accepted. And this became evidence that the  use of role playing mode is effective to enhance student’s speaking skill.